2017
DOI: 10.1111/dom.13068
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial long‐term antidiabetic actions of N‐ and C‐terminally modified analogues of apelin‐13 in diet‐induced obese diabetic mice

Abstract: These data indicate the therapeutic potential of stable apelin-13 analogues, with effects equivalent to or better than those of exendin-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…Consistent with this view, recent work in our laboratory has shown that therapeutic natural and stable analogues of apelin-13 stimulate insulin secretion, enhance cellular glucose uptake and improve acute glucose tolerance in animal models of obesity-diabetes [ 27 , 34 ]. Native apelin undergoes extensive enzymatic degradation and rapid plasma clearance in vivo .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Consistent with this view, recent work in our laboratory has shown that therapeutic natural and stable analogues of apelin-13 stimulate insulin secretion, enhance cellular glucose uptake and improve acute glucose tolerance in animal models of obesity-diabetes [ 27 , 34 ]. Native apelin undergoes extensive enzymatic degradation and rapid plasma clearance in vivo .…”
Section: Discussionmentioning
confidence: 82%
“…Numerous studies indicate an emerging involvement of apelin in energy metabolism and the pathophysiology of obesity [ 39 42 ]. Both apelin and APJ receptors are present in many tissues including mouse, human and rat adipose tissue and pancreatic islets [ 20 ; 34 , 43 , 44 ]. Circulating apelin concentrations are increased in obese humans and rodent models of obesity only when accompanied by hyperinsulinaemia [ 20 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the present study has shown that once daily administration of (Lys 8 gluPAL)apelin-13 amide or pGlu(Lys 8 gluPAL)apelin-13 amide ameliorated diabetes, evoked weight loss and decreased circulating lipids in DIO mice, with effects equivalent to or better than liraglutide. Overall the pGlu(Lys 8 gluPAL)apelin-13 amide was the most effective analogue and was better than it equivalent nonacylated analogue tested previously [7].…”
Section: Discussionmentioning
confidence: 75%
“…The improvements may also reflect improvement in insulin action as evidenced by enhanced hypoglycaemic action of exogenous insulin. Apelin and its APJ receptors have been detected in the arcuate and paraventricular nuclei of hypothalamus, known to be key sites in central control of feeding behaviour and energy expenditure [7,8]. Apelin could also alter body adiposity independent of food intake by increasing energy expenditure [9].…”
Section: Discussionmentioning
confidence: 99%